Reflections on state, education and development: On the subject of a World Meeting of Educators - Vargas Contreras, Felipe (1993)
Between the months of August and September 1992, thanks to the travel experience and participation in the IV World Meeting of African Teaching Teams, we were able to appreciate the contrasts of different educational realities and standards of living between the peoples of the Third World and developed Europe. Côte d'Ivoire is a country located on the Atlantic coast, integrated into the central western African region that looks from afar at the Guianese coasts and the Brazilian northeast.